Correlation Between Perception-Based Journal Rankings and the Journal Impact Factor (JIF): A Systematic Review and Meta-Analysis. Issue 2 (3rd April 2017) - Mahmood, Khalid
ABSTRACT: This study, based on systematic review and meta-analysis, aimed to collect and analyze evidence on correlation between perception-based journal rankings and the most popular citation-based measure, Thomson Reuters Journal Impact Factor (JIF). A search was conducted in the Web of Science, Scopus, and Google Scholar databases. After the screening of titles, abstracts, and full text, 18 articles were selected as eligible for review and analysis. The included studies belonged to various subject areas in social sciences, science, and technology. The correlation coefficients found in most of the studies were statistically significant in a positive direction. The heterogeneity test was positive. Therefore, the random-effect method of meta-analysis was applied. The value of pooled correlation coefficient indicated a moderate positive relationship between two methods of assessing the quality of academic journals. The absence of a high correlation makes decision making based on a single ranking method dangerous. Therefore, a hybrid approach for journal assessment is recommended.